2010
DOI: 10.1259/bjr/68875123
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and visualisation of focal cartilage thickness change by MRI in a study of knee osteoarthritis using a novel image analysis tool

Abstract: ABSTRACT. We describe the application of a novel analysis method that provides detailed maps of changes in cartilage thickness measured from MRI scans for individuals and cohorts of patients together with regional measures. A cohort of osteoarthritis patients was imaged using a 1.0 T MR scanner over a 36-month period. Hyaline cartilage was manually segmented from a three-dimensional (3D) spoiled gradient-echo sequence with fat suppression. Representative outlines of the bone surfaces of the distal femur and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…We did not observe similar associations between lateral cartilage thickness loss or the dGEMRIC index with weight loss. The differential change in the medial compared with the lateral compartment is not unexpected as previous studies have found that the medial compartment generally exhibits higher rates of cartilage loss in people with knee OA 31 34 35. This finding is likely to be attributable to the greater proportion of ground reaction forces borne by the medial tibiofemoral compartment, even in normally aligned knees 36.…”
Section: Discussionmentioning
confidence: 70%
“…We did not observe similar associations between lateral cartilage thickness loss or the dGEMRIC index with weight loss. The differential change in the medial compared with the lateral compartment is not unexpected as previous studies have found that the medial compartment generally exhibits higher rates of cartilage loss in people with knee OA 31 34 35. This finding is likely to be attributable to the greater proportion of ground reaction forces borne by the medial tibiofemoral compartment, even in normally aligned knees 36.…”
Section: Discussionmentioning
confidence: 70%
“…The semi-automated approach used the following method. First, the user selected start and end sagittal images for each major cartilage region (femoral, medial tibial, lateral tibial and patellar), as well as seed points in the subchondral bone midway between the two slices 25 26. Initial boundary finding for the bone–cartilage interface was performed by an active contour approach.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 176 sagittal 3D double‐echo steady state (DESS) MR images from 2 scans of 88 knees (baseline and 12‐month follow‐up visits) in the Osteoarthritis Initiative (OAI) database were used in this study. All knees had manual segmentations of cartilage and menisci supplied by Imorphics . The relevant scan parameters for DESS were as follows: field of view = 14 cm, matrix = 384 × 307 (zero‐filled to 384 × 384), echo time = 5 ms, repetition time = 16 ms, 160 slices with a thickness of 0.7 mm.…”
Section: Methodsmentioning
confidence: 99%